The future scribe: Learning to write the world - Lindberg, Ylva; Öberg, Lena-Maria (Frontiers in Education, 2023)
This study takes its point of departure in academic scholarship that points to how programming – reading and writing code – is the literacy of the future, in other words, non-specialized competence that should be acquired in education in parity with traditional reading and writing skills. The goal is to shed light on how programming can be orchestrated in education to break with the outworn dichotomy between the ‘two cultures’ that C. P. Snow formulated as a gap between, on the one hand, natural sciences, mathematics, and technology, and, on the other hand, the humanities, and social sciences. A discursive analysis of Swedish policy documents and curricula forms the empirical ground for discussing how reading and writing code are introduced, taught, and learnt within Swedish compulsory school. The results show that Swedish curricula are framing programming as specialized knowledge within technology and mathematics, rather than allowing it to be a dimension of several subjects, such as the humanities and social sciences. These findings are discussed in the light of recent studies in education that have explored interrelations between coding and reading and writing texts. The discussion leads up to suggestions for implementing reading and writing code as digital literacy in education.